Library Service Innovation as Learning Media at The Universitas Terbuka Distance Education Library - Mohamad Pandu Ristiyono (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Long before Covid 19 hit the world, the Universitas Terbuka library already had online services as a learning media With rapid technological advances, the world is now entering the era of the Industrial Revolution 4.0, where synchronous learning can be done not only face-to-face in traditional classes, but also through distance education with the help of technology. Universitas Terbuka that use distance learning for their students are spread throughout the archipelago and in 52 countries. In lectures at the Universitas Terbuka (UT), Modules (teaching materials) function as representatives of lecturers for students, but since the digital era, UT has conducted online tutorials (Tuton) to connect students with lecturers (Tutors). Similarly, UT has provided electronic library services. Virtual Reading Room (RBV) and Tuweb and Streaming services. Tuweb and streaming services have a positive impact on students.